SIMULASI AERODINAMIKA DESAIN MOBIL HEMAT BAHAN BAKAR ‘ANTAWIRYA’ DENGAN METODE COMPUTATIONAL FLUID DYNAMICS - Abdul Hadi Hanif; MSK. Tony Suryo Utomo (JURNAL TEKNIK MESIN, 2015)
Increasingly depleted world’s oil deposit has encouraged the automotive industry, including the government and universities, to be more innovative in their efforts to find a breakthrough. More aerodynamic vehicle design will produce a smaller drag coefficient value, thus reducing fuel consumption. The purpose of this research is to get the magnitude of the drag coefficient as low as possible in the design of ‘Antawirya’ fuel efficient car. It focuses on the phenomenon of fluid flow that takes place all around the car and the effort to create a more aerodynamic car body design. Car aerodynamics simulations are conducted in the wind tunnel set as the computing domain by Computational Fluid Dynamics. The k-epsilon realizable standard wall function method is used in this research, which is specified based on the phenomenon of validation in backward-facing step by knowing the separation and the reattachment point on these phenomena. This research also uses the second order upwind as the discretization method for more accurate results. The number of each grid for previous Antawirya and Antawirya konsep 1 are 862391 and 767870. The results of the simulation show a reduction of drag coefficient on Antawirya konsep 1 compared to the previous Antawirya. Drag coefficient has shown a decrease by 38,18 % from 0,385 into 0,238 at a rate of 10 km/h, a decrease by 39,14 % from 0,373 into 0,227 at 20 km/h, a decrease by 39,84 % from 0,369 into 0,222 at 30 km/h, a decrease by 40,27 % from 0,365 into 0,218 at 40 km/h, a decrease by 40,38 % from 0,364 into 0,217 at 50 km/h, and a decrease by 40,27 % from 0,360 into 0,215 at 60 km/h. The separation and wake phenomenon also occurred on the back of the car body as the separation and wake on Antawirya konsep 1 are shorter than the previous Antawirya design. This is due to the fact that the body of Antawirya konsep 1 has a more aerodynamic design.